PEMODELAN CALON GURU FKIP UNMAS DENPASAR MELALUI LESSON STUDY BERBASIS HABIT FORMATION LEARNING SYSTEM - Kumara, Dewa Gede Agung Gana (Fakultas Keguruan dan Ilmu Pendidikan (FKIP) Universitas Mahasaraswati Denpasar, 2017)
The purpose of this study was to determine the level of students’ competence of SMP Tangeb majoring in sculpture through the lesson study Habit-based formation Learning System involving teachers, lecturers and prospective teachers. This research method used classroom action approach through lesson study. The research process spanned two cycles. Instruments used in data collection included assessment of teaching practice, chararacter check list, questionnaire and participant observation sheet. The effectiveness of the approach could be analyzed to what extent was the average score of 38 students collected randomly in each cycle increased from the initial test score after the lesson was applied. The indicator of research success or research outcome target was where 80% of students achieved the average value above the minimal mark that was 75. From the PAP range of students’ achievement, students that reached the high criteria were 21 people while the moderate criteria were 17 people. From students’ learning attitude could be seen that 30 students (86%) were active, 33 (87%) were cooperative and students that were responsible were 36 students (94%). From this result, it could be said that the ability of VII grade students of SMP Seni Ukir Tangeb in attitudes of learning, knowledge and writing skills of English was in high category and above entrepreneurial attitude that was 50%. Thus the lesson study based on the formation of this habit could improve the English language skills of VII students of SMP Seni Ukir and their attitude in learning was more characteristic.